Malaria parasites differentially sense environmental elasticity during transmission - Ripp, Johanna; Kehrer, Jessica; Smyrnakou, Xanthoula; Tisch, Nathalie; Tavares, Joana; Amino, Rogerio; Ruiz de Almodóvar, Carmen; Frischknecht, Friedrich (EMBO molecular medicine, 2021)
Transmission of malaria-causing parasites to and by the mosquito relies on active parasite migration and constitutes bottlenecks in the Plasmodium life cycle. Parasite adaption to the biochemically and physically different environments must hence be a key evolutionary driver for transmission efficiency. To probe how subtle but physiologically relevant changes in environmental elasticity impact parasite migration, we introduce 2D and 3D polyacrylamide gels to study ookinetes, the parasite forms emigrating from the mosquito blood meal and sporozoites, the forms transmitted to the vertebrate host. We show that ookinetes adapt their migratory path but not their speed to environmental elasticity and are motile for over 24 h on soft substrates. In contrast, sporozoites evolved more short-lived rapid gliding motility for rapidly crossing the skin. Strikingly, sporozoites are highly sensitive to substrate elasticity possibly to avoid adhesion to soft endothelial cells on their long way to the liver. Hence, the two migratory stages of Plasmodium evolved different strategies to overcome the physical challenges posed by the respective environments and barriers they encounter.
Gesehen am 09.03.2021